ANALISIS KONFIGURASI SPASIAL DAN HIERARKI PRIVASI PADA TIPOLOGI HUNIAN MENENGAH DI KOTA BATAM DENGAN PENDEKATAN SPACE SYNTAX (STUDI KASUS: AGUNG PERMAI RESIDENCE) - Jeanny Laurens; Hendro Murtiono; I Gusti Ngurah Anom; Carissa Dinar Aguspriyanti (Journal of Architectural Design and Development (JAD), 2026)
The rapid development of cluster housing in Batam City is generally dominated by standard design typologies which have mass produced by developers. The aim of the mass produced is for construction efficiency. Design evaluation is often limited to facade aspects, neglecting the internal spatial configuration underlying social interaction and occupant privacy. This study aims to analyze the spatial configuration and privacy hierarchy of four standard house type in Agung Permai Residence, those are type 40, type 48, type 78 and type 108. A quantitative descriptive method was used through a space syntax approach by extracting floor plans into Justified Permeability Graphs (JPG) and also mathematical calculations focused on Mean Depth (MD) and Integration Value (i). The result indicates that an increase building area in single-story dwellings (type 40 to type 48) does not alter the shallow centralized graph structure pattern, resulting in high vulnerability to visual intrusion in private areas. On the contrary, a fundamental improvement in privacy hierarchy quality is only achieved in two-story dwellings (type 78 and type 108), where the vertical circulation element, be inform of stairs, successfully acts as a spatial filter creating a deep graph structure. These theoretical findings recommend a reorientation of circulation design in small type housing to secure family domestic boundaries.